The Benefits of Intermittent Fasting as an Alternative to Medical Therapy to Improve Health Status - Amiruddin, Muhammad; Oktavia, Reza Putri; Hidayat, Hakmi (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Health is a fundamental human need to be cared for. In order to maintain health of the body, there is one alternative medicine growing around the community, a therapy performed by the prophet Muhammad SAW or commonly known as thibbun nabawi. The example of the prophet’s teaching and actions included in pillars of islam is fasting. Fasting in addition to increase faith and taqwa, can also benefit from the fasting. Objectif: The purpose of this research was for communities to understand fasting and health relationships for the next time being practiced in live. Methods : The research method used was literature review. As for the nature of this studt is a descriptive analysis, which is a regular break from fasting to health, then an explanation is given for the reader to read well. Results: The study result in that fast devoted to disease are called Intermittent fasting. The detoxification process will occur naturally in the human body that regularly performs intermittent fasting, eventually improving its resistance. Conclusion : The conclusion is that intermittent fasting can improve health status, either improving body immunity and or disease treatment. It must also be offset by implementing a healthy lifestyle.